2021
DOI: 10.1038/s41598-021-96102-3
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of a novel cold-resistance protein 1 from Brassica oleracea promotes tolerance to chilling stress in transgenic tomato

Abstract: Cold stress is considered as one of the major environmental factors that adversely affects the plant growth and distribution. Therefore, there arises an immediate need to cultivate effective strategies aimed at developing stress-tolerant crops that would boost the production and minimise the risks associated with cold stress. In this study, a novel cold-responsive protein1 (BoCRP1) isolated from Brassica oleracea was ectopically expressed in a cold susceptible tomato genotype Shalimar 1 and its function was in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Recently, Kashyap et al [73] showed an ICE homolog, BjICE53, to be involved in the cold signaling pathway in Brassica juncea. They revealed conserved domains and motifs that bind to the CRT/DRE motifs of BjCBF for the expression of downstream cold-regulatory genes [74][75][76]. Another study in Chrysanthemum morifolium, "Jinba", demonstrated that overexpression of CmICE2 in transgenic Arabidopsis induces the expression of downstream cold regulatory genes (AtCBF1/2, AtCOR6.6a/414, and AtKIN1), leading to cold stress tolerance through increased proline contents, superoxide dismutase (SOD) activities, and elevating catalase (CAT) levels [77].…”
Section: Inducer Of Cbf Expression (Ice)mentioning
confidence: 99%
“…Recently, Kashyap et al [73] showed an ICE homolog, BjICE53, to be involved in the cold signaling pathway in Brassica juncea. They revealed conserved domains and motifs that bind to the CRT/DRE motifs of BjCBF for the expression of downstream cold-regulatory genes [74][75][76]. Another study in Chrysanthemum morifolium, "Jinba", demonstrated that overexpression of CmICE2 in transgenic Arabidopsis induces the expression of downstream cold regulatory genes (AtCBF1/2, AtCOR6.6a/414, and AtKIN1), leading to cold stress tolerance through increased proline contents, superoxide dismutase (SOD) activities, and elevating catalase (CAT) levels [77].…”
Section: Inducer Of Cbf Expression (Ice)mentioning
confidence: 99%
“…In response to cold stress, the abscisic acid (ABA), jasmonic acid (JA), and indole acetic acid (IAA) are among the phytohormones involved in activating CBF-dependent signaling pathway ( Wang et al, 2021 ; Zhou et al, 2021 ; Fu et al, 2022 ). The interaction between CBF and CRT/DRE motif regulates the downstream expression of an array of COR genes, which belong to KIN (cold induced), RD (responsive to desiccation), LTI (low temperature induced), and ERD (early dehydration inducible; Wani et al, 2021 ). The regulated products of COR genes include osmo-protectants biosynthetic enzymes, late embryogenesis abundant (LEA) proteins, TFs, protein kinases, proteins associated with lipid metabolism, proteins for hormone responses, cell wall modifiers, and chloroplast proteins ( Liu et al, 2019 ).…”
Section: Early and Late Cold Stress Response By Transcription Factorsmentioning
confidence: 99%
“…For each qPCR reaction, 1 μl of cDNA diluted by a factor of 10 was mixed in a 0.2 ml RNase free tube containing 6 μl of 2X Syber green, 0.3 μl each of forward and universal reverse primer, and 4.4 ml Milli-Q water. The reaction mixture was run in lightCycler480-II (Roach) and the fold chnage was calculated using 2 −∆∆CT method [ 16 ].…”
Section: Main Textmentioning
confidence: 99%